Cheaper cement formulation for lost circulation control - Samsuri, Ariffin; Phuong, B. T. N. (2002)
Laboratory experiments had been carried out by using G and special blended cement with various amount and types of standard cement additives and various amount of local bentonite and sugar cane fiber. The ASTM-C 114 and AAS procedures were used for the chemical analysis and API Spec. 10 procedures under atmospheric and reservoir conditions for the cement performance. One of the serious cementing problems is a lost circulation whoch may occur in high permeability, formation, vugs or naturally fractured formation. Therefore this study focused on development of a cement mixture to overcome lost circulation problem and also strong enough to hold casing with minimize damage to potential producing formation. The results shown that optimum size of local bentonite ranging from 150-250Î¼m and sugar cane fiber ranging from 2000-2800Î¼m. A suitable cement system formulation for optimum lost circulation control is 9% local bentonite, 2% calcium chloride and 0.5 sugar cane fiber with adequate shear bonding strength and formation permeability reduction is about 10%. Generally, special blended cement has less free water and fluid loss, better strength development but shorter thickening time than G cement. The cost of blended cement is cheap, bentonite is a local material and sugar cane fiber is a waste material, therefore there will be about 48% of the cement material cost saving if this cement formulation is used for an average oil well at 8000ft depth. This formulation also proves to be the cheaper choice for cementing job, particularly the shallow well due to the shorter thickening time.